2016
DOI: 10.14257/ijast.2016.94.07
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Comparison of Fluid Jet Impingement Heat Transfer on Flat Plate Using CFD

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Krishna Varma et al [2018] carried optimized the process parameters of cooling of an engine radiator using Taguchi optimization. Mohan et al [2017] carried out CFD simulations to analyze the impingement of rectangular jet on a flat plate using nanofluids. It was also found that in the literature, the low volume concentrations of nanofluids provide higher efficiencies and most of the studies on nanofluids were focused on the investigations carried out at low volume concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Krishna Varma et al [2018] carried optimized the process parameters of cooling of an engine radiator using Taguchi optimization. Mohan et al [2017] carried out CFD simulations to analyze the impingement of rectangular jet on a flat plate using nanofluids. It was also found that in the literature, the low volume concentrations of nanofluids provide higher efficiencies and most of the studies on nanofluids were focused on the investigations carried out at low volume concentrations.…”
Section: Introductionmentioning
confidence: 99%